The Role of Incentives to Achieve Job Satisfaction for Staff at the University of Zakho - Ouso, Khairi A.; Haji, Avan Y.; Dino, Chiya I. (Humanities Journal of University of Zakho, 2018)
The starting point of the scheme supposedly takes into account the direction of the relationship between two variables, In order to achieve the goal of the research and complete the requirements of researchers began preparing a theoretical framework to benefit from the literature, And adopted in this research descriptive analytical method, questionnaire was used to solicit the views of the research sample, Consisting of staff who numbered ( 53) employees, some were used statistical methods to analyze the results and test hypotheses, The results of the study, The most important conclusions of the low satisfaction levels of staff at the University for salaries and wages granted to them, and as well as the weakness or the limited presence of justice at distribution work among staff in academic departments of the University, The research found a set of proposals represented the most important of the need to achieve satisfaction for employees, especially with regard to salaries and wages granted to them, As well as the achievement of justice at distribution work among staff in academic departments of the University.